PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA DOSEN FAKULTAS EKONOMI UNIVERSITAS TRIDINANTI PALEMBANG - Agustina M (JURNAL KOMPETITIF, 2014)
University of Tridinanti Palembang is one of education implementing units owned by private in Palembang. Where during its development period, University of Tridinanti Palembang has experienced ups and downs. Related with that, this thesis in general discuss about how the Performance of Faculty of Economy University of Tridinanti Palembang Lecturers is, if seen from Leadership Manner and Interpersonal Communication. Therefore, the purpose of this research is to know the influence of Leadership Manner and Interpersonal Communication towards the Performance of Faculty of Economy University of Tridinanti Palembang Lecturers.Based on the result of F-count, it is obtained 30,348 or a significance of 0,000 < alpha = 0, 05. Due to the significance rate of < 0,05, thus it can be said that tested hypothesis Ho is rejected and Ha is accepted. Means that there is a positive and significant influence of Leadership Manner (X1) and Interpersonal Communication (X2) towards the Performance (Y) of Lecturers together. The amount of influence together is 56,4% and the rest of 43,6% is influent by other variable which is not inspected by this research. There is a positive and significant influence of Leadership Manner towards the Performance of Lecturers. This is seen from the t-count result of 2,129 with significance of 0,039 which means < alpha = 0,05, that the influence of Leadership Manner is positive in significant. There is a positive and significant influence of Interpersonal Communication towards the Performance of Lecturers. This is seen from the t-count result of 7,182 with significance of 0,000 which means < alpha = 0,05, that the influence of Interpersonal Communication towards the Performance of Lecturers is positive and significant. Thus it can be said that tested hypothesis Ho is rejected and Ha is accepted. Means that there is positive and significant influence of Interpersonal Communication towards the Performance of Faculty of Economy University of Tridinanti Palembang Lecturers. Keywords: Performance, Style Leadership, Interpersonal CommunicationÃ‚Â